Why social scientists still need phenomenology. (February 2022) - Houston, Christopher
Pierre Bourdieu famously dismissed phenomenology as offering anything useful to a critical science of society – even as he drew heavily upon its themes in his own work. This paper makes a case for why Bourdieu's judgement should not be the last word on phenomenology. To do so it first reanimates phenomenology's evocative language and concepts to illustrate their continuing centrality to social scientists' ambitions to apprehend human engagement with the world. Part II shows how two crucial insights of phenomenology, its discovery of both the natural attitude and of the phenomenological epoche, allow an account of perception properly responsive to its intertwined personal and collective aspects. Contra Bourdieu, the paper's third section asserts that phenomenology's substantive socio-cultural analysis simultaneously entails methodological consequences for the social scientist, reversing their suspension of disbelief vis-à-vis the life-worlds of interlocutors and inaugurating the suspension of belief vis-à-vis their own natural attitudes.